Incidence of Dural Injury during Craniotomy - a Single Center Study - Limbu, Punam; Dhimal, Kaushila; Biswakarma, Pushpa (Eastern Green Neurosurgery, 2020)
Background: During a craniotomy, there is a high chance of unintentional dural tear and may occur in both layers or only in the outer layer.ith the objective to see the incidence of dural tear during craniotomy using high-speed craniotome, this study was performed.Materials and methods: This is a prospective analytical study collected over the duration of 4 months. Cases of craniotomy done using the craniotome were collected. Age was presented as mean and standard deviation (S.D). Gender, diagnosis, and dural tear were presented in frequencies and percentages. Analysis of gender, diagnosis categories, and age categories with a dural tear was done using the Fischer exact test. Similarly, Pearson's correlation was done between the number of burr holes made and dural tear in SPSS20. Results: There were a total of 25 craniotomies performed during the study period using craniotome. The mean age of presentation was 43.32 (17.65) years. The incidence of the dural tear was noted in 20% of the cases which includes a single layer or both the layers of the dura. There was a significant association between different age categories and dural tear; where elderly patients seem to have more percentage of the dural tear.Conclusion: There was a 20% incidence of dural tear during craniotomy with a significantly higher incidence in the elderly population.